Le limonène dans les huiles essentielles : énantiomères et activités biologiques - Aribi-Zouioueche, Louisa (Comptes Rendus. Chimie)
Literature data are used to identify the enantiomeric diversity of limonene in 54 essential oils composed of between 0.3–99.7% of this molecule. Significant enantiomeric excesses are observed, either in (R)-(+)-, or in (S)-(–)-limonene, and more rarely, the two enantiomers in equal proportion. The olfactory properties of these enantiomers, as well as the impact of the enantiotype on the biological and toxicological activities of limonene are reported. The distribution of the two enantiomers in nature is balanced, however, only the (R)-(+)-limonene enantiomer, from citrus fruits, is exploited and valued. The main body of research that targets the (R)-(+)-limonene enantiomer in the development of natural medicine for health improvement is reported. The biological and toxicological activities of the enantiomers of limonene are compared, whether they are isolated, or combined with other components of essential oils. The identification of the enantiotype is valuable information that allows better visibility and safer use of essential oils.